24.7k views
1 vote
1. -3( x - 4) = 2x + 4 - x

2. 4 + 2 (x - 2) = 2 (x - 1) + 2
3. 3(x - 4) = 2x - 7 + x
4. 4x + 15 = 3(x + 5)
5. 2(x - 3)
——————- = x
4

6. 4x - 3
—————-— = 2x - 1.5
2

1 Answer

4 votes

Answer:

Explanation:

1. -3( x - 4) = 2x + 4 - x

-3x + 4 = x + 4

4 = 2x + 4

2x = 0

x = 0

2. 4 + 2 (x - 2) = 2 (x - 1) + 2

4 + 2x - 4 = 2x + 2 + 2

2x = 2x + 4

x = 4

3. 3(x - 4) = 2x - 7 + x

3x - 12 = 3x - 7

x = 5

4. 4x + 15 = 3(x + 5)

4x + 15 = 3x + 15

x = 0

5. 2(x - 3)

for the rest i'm confuse what it is suppose to be

User Psmagin
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.